2011
DOI: 10.1007/s11121-011-0204-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study into the Costs and Impact on Family Functioning of 4-Year-Old Children with Aggressive Behavior

Abstract: Early-onset aggressive behavior is known for its negative developmental consequences, and the associated high costs for families, the health care system and wider society. Although the origins of aggressive behavior are to be found in early childhood, the costs incurred by aggressive behavior of young children have not been studied extensively. The present study aimed to investigate whether preschool children with a high level of aggressive behavior already differ in the generated amount of costs and impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…Emotional and behavioral problems in early childhood are a major public health concern (National Research Council and Institute of Medicine, ) and are associated with later problems with school achievement, social relationships, and workforce potential (Guyer et al., ; National Forum on Early Childhood Policy and Programs, ; National Scientific Council on the Developing Child, ). Untreated, these problems impose significant emotional and economic costs and burdens to individuals, families, and society (Raaijmakers, Posthumus, van Hout, Van Engeland, & Matthys, ; Scahill, ). A variety of individual, family, and environmental factors have been identified that place children at increased risk for the development of emotional and behavioral problems (Gorman‐Smith, ; Youngstrom, Weist, & Albus, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional and behavioral problems in early childhood are a major public health concern (National Research Council and Institute of Medicine, ) and are associated with later problems with school achievement, social relationships, and workforce potential (Guyer et al., ; National Forum on Early Childhood Policy and Programs, ; National Scientific Council on the Developing Child, ). Untreated, these problems impose significant emotional and economic costs and burdens to individuals, families, and society (Raaijmakers, Posthumus, van Hout, Van Engeland, & Matthys, ; Scahill, ). A variety of individual, family, and environmental factors have been identified that place children at increased risk for the development of emotional and behavioral problems (Gorman‐Smith, ; Youngstrom, Weist, & Albus, ).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of externalizing behavior (e.g., aggression, oppositional behavior, disobedience) in the early years of life forecasts a variety of problems later in childhood (Campbell et al., ). Left untreated, externalizing behavior often worsens with age and tends to persist over time (Mesman, Bongers, & Koot, ; Vaughn, Salas‐wright, Delisi, & Maynard, ), generating substantial social and economic costs to individuals and society (Raaijmakers, Posthumus, Van Hout, Van Engeland, & Matthys, ; Scott, Knapp, Henderson, & Maughan, ). These observations underscore the importance of early intervention to ameliorate such early emerging problems.…”
Section: Parenting and Externalizing Behaviormentioning
confidence: 99%
“…ODD and CD are among the most prevalent psychiatric disorders in children and adolescents, with percentages of 3.2 for ODD and 2.0 for CD (Lahey et al 1999). In addition to the negative developmental consequences of ODD and CD for the individual, such as poor interpersonal and school adjustment, delinquency, substance use disorders, and other psychiatric disorders (Kim-Cohen et al 2003;Maughan and Rutter 2001), these disorders also incur high costs to society (Raaijmakers et al 2011;Scott et al 2001). Conceptual developmental models are needed as they can identify active mechanisms, which can be targets of preventive and treatment interventions for ODD and CD youth (Matthys and Lochman 2010).…”
Section: Introductionmentioning
confidence: 99%